18F‐fluorodeoxyglucose positron emission tomography findings of peripheral nerve sheath tumour of the nasal cavity in a dog. Issue 2 (10th January 2023) - Lee, Dohee; Yun, Hyejin; Yun, Taesik; Koo, Yoonhoi; Chae, Yeon; Nam, Hyeyeon; Kang, Seonggweon; Lee, Hayoon; Chang, Dongwoo; Yang, Mhan‐Pyo; Kang, Byeong‐Teck; Kim, Hakhyun
Abstract: An 8‐year‐old Miniature Poodle presented with chronic sneezing and unilateral epistaxis. A left‐sided intranasal mass was identified on computed tomography. 18F‐fluorodeoxyglucose (FDG) positron emission tomography (PET) was performed to evaluate the metabolic activity of the mass. The intranasal mass showed mildly increased 18F‐FDG uptake. The maximal and mean standardized uptake values (SUVs) of the mass were 3.4 and 2.6, respectively. The maximal SUV of the mass/mean SUV of the normal liver was 2.5. The 7‐cm soft, pink mass was easily removed through rhinoscopy, with subsequent dramatic improvement in clinical signs. Histopathological and immunohistochemical analyses determined that the mass was an intermediate‐grade malignant peripheral nerve sheath tumour (PNST). This is the first report of 18F‐FDG PET findings in a PNST in dogs. Abstract : An 8‐year‐old Miniature Poodle was presented with chronic sneezing and unilateral epistaxis. 18F‐fluorodeoxyglucose (FDG) positron emission tomography was performed, and the dog was finally diagnosed to an intermediate‐grade malignant peripheral nerve sheath tumor based on the histopathologic examination. This is the first report of 18F‐FDG PET findings in a malignant PNST in dogs.